2018
DOI: 10.1088/2040-8986/aacdeb
|View full text |Cite
|
Sign up to set email alerts
|

Self Q-switched mode-locking in compact red Pr3+-doped ZBLAN fiber laser

Abstract: The self Q-switching mode-locking effect in compact red fiber laser has been investigated. The Q-switched mode-locking state can keep operating with a pump power ranging from 120.5 mW to 564.8 mW. The maximum average output power of this self Q-switched mode-locking laser is 22.5 mW, and the central wavelength of the output optical spectrum is 635.9 nm with a 3 dB bandwidth of 2.4 nm, as well as the fundamental repetition rate of mode-locking pulse trains being 25.8 MHz. This work can provide an attractive met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…At lower pump powers, the front part of the FM-EDF provides gain while the later part absorbs the signal. Once the pump power reaches one critical value, the saturable absorption just disappears [33]. Due to the 'distributed nature' [34] of saturable absorption of signal along the FM-EDF, we observed that the amplitude of the QS envelop experienced a weak fluctuation.…”
Section: Multimode Qml Operationmentioning
confidence: 83%
See 1 more Smart Citation
“…At lower pump powers, the front part of the FM-EDF provides gain while the later part absorbs the signal. Once the pump power reaches one critical value, the saturable absorption just disappears [33]. Due to the 'distributed nature' [34] of saturable absorption of signal along the FM-EDF, we observed that the amplitude of the QS envelop experienced a weak fluctuation.…”
Section: Multimode Qml Operationmentioning
confidence: 83%
“…However, there appeared a train of chaotic pulses every few seconds. The phenomenon can be interpreted as follows: with the increment of the pump power, there was a reduction of saturable absorption for the signal, the saturable absorption effect disappeared finally at high pump power, and therefore the QML pulsation was eliminated [33,38]. Further increasing the pump power by 2 mW, the laser output became a chaotic state completely.…”
Section: Multimode Qml Operationmentioning
confidence: 99%
“…Jung et al also obtained burst pulse in a bismuth-doped germanosilicate fiber ring laser through self Q-switched mode-locking [10]. Wu et al demonstrated burst pulse output in Pr 3+ -doped ZBLAN fiber linear laser based on self Q-switched mode-locking [11]. To control the number of pulses in each burst, an acousto-optic modulator (AOM) is used to select groups of seed pulses from the 50 MHz pulse train from ytterbium-doped fiber laser [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, recent work show that, relatively stable operation could potentially also be achieved in QML regime [45,46], a stability range that is sufficient enough for many applications where the process also averages out the fluctuations. QML operation have been described in many laser gain media, including Nd:fiber [47], Nd:YVO 4 [46,48,49], Nd:GYSGG [50], Nd:LuVO 4 [45], Tm-doped aluminum oxide glass [51], Tm:CYA [52], Er:YAG [53], Er-doped fiber [54], Prdoped ZBLAN fiber [55]. Various Q-switched mode-locking mechanisms such as nonlinear interferometry [51], MoS2 saturable absorbers [52], self QML [55], saturable Bragg reflectors [53], graphene-oxide [50,54], liquid dye solution [47], Cr:YAG [45,46], V:YAG [46], LiF [46,49], GaAs [46], and acousto-optic modulators [46,48] have been employed in these earlier work.…”
Section: Introductionmentioning
confidence: 99%